Community pharmacy’s role in dispensing androgens and supporting harm reduction amid current policy dilemmas - Timothy Piatkowski; Lkhagvadulam Ayurzana; Michelle King; Laetitia Hattingh; Sara McMillan (Substance Abuse Treatment, Prevention, and Policy)
Abstract Background Legitimate androgen use, such as testosterone replacement therapy, requires a legal prescription. Off-label use for reasons like wellness and aesthetics continues to grow. Recent regulatory changes in Australia aim to curb non-prescribed androgen use, potentially intensifying stigma, however seeking prescriptions through legal channels persists. This study aimed to explore community pharmacists’ knowledge, attitudes, and practices regarding individuals who use androgens. Methods We conducted semi-structured interviews with 15 community pharmacists, to explore knowledge and experiences related to the dispensing of androgens. The data analysis followed an iterative process, developing a codebook for thematic analysis and aligning findings with relevant literature. Results Pharmacists face challenges when meeting the needs of individuals using androgens. They often made judgments based on appearance, leading to stigmatisation and potential refusal of prescription supply. However, this is tempered by the complex environment that pharmacists work in with respect to professional and legal requirements. Limited knowledge about androgens and varying exposure to people who use androgens were evident, prompting a unanimous desire for tailored training, especially in communication skills and interaction strategies. Conclusions Facilitating androgen use within regulated healthcare settings, under professional medical supervision, is crucial to mitigating health risks. Varied pharmacist knowledge underscores the urgent need for targeted training, emphasising education initiatives to address structural stigma and inform healthcare policies globally.